Analisis Deret Waktu Data Perencanaan Tenaga Kerja pada Perusahaan Manufaktur Menggunakan Model ARIMA - Yusapra Salim, Asep; Yuliani, Mila; Andayani Komara, Mutiara; Sri Wahyuni, Rani (Jurnal Teknologika, 2024)
In the industrial world, forecasting is a very important part to be used as a basis for strategic planning, business growth, revenue projections, and decision-making of an organization or company. Manpower planning or workforce planning, is indeed crucial for organizations of all sizes. It involves strategically analyzing and forecasting an organization's current and future workforce needs to ensure that it has the right number of employees with the appropriate skills in the right roles at the right time. One of the analyses that can be used for forecasting is data analysis using the Time Series Method. One aspect that can be analyzed is Man Power Planning in the Manufacturing Company. By knowing the forecasting, workforce planning can be measured in terms of productivity, efficiency, and sustainability of the organization's or company's operations. This data has been analyzed using the ARIMA Model, which can produce comparative data as a data reference to support further decisions for the Manufacturing Company. The results of this analysis provide valuable guidance for company management in making decisions related to human resource planning, including: optimizing productivity, reducing operational costs, and increasing the efficiency of the company's overall operations.